Online Vs Offline: Comparison of Effectiveness of PhET Simulation and Science KIT in Junior High School - Firda Nikmah; Maison Maison; Syamsurizal Syamsurizal (Integrated Science Education Journal, 2023)
Purpose of the study: This study aims to compare the effectiveness of online and offline simulation media. Especially during the transition period from the new normal, hybrid learning and back to the new normal. Methodology: The research design used was quasi-experimental. The study sample was taken using a random sampling technique. The data collection techniques used are observation and tests. Observation is carried out to find out more about the subject of research. A trial is conducted to determine the condition of students before and after receiving treatment. There are two test instruments used, namely pretest and posttest. The treatment given to the control class is learning using Science KIT, and the experimental class will use PhET Simulation. The results of the study will be processed using SPSS. Main Findings: PhET media and science KIT based on the N-gain test proved to increase on average after treatment. In the control class, the gain value was 0.7, while the gain value was 0.8 in the experimental class. According to the criteria, both classes are in the high category. but in contrast to the percentage of effectiveness, the use of PhET is effective with a rate of 86%, while KIT science is quite practical with a ratio of 71%. Novelty/Originality of this study: PhET simulation media and science KIT can explain abstract material to improve cognitive understanding. The use of this simulation media can be adjusted to learning conditions. if offline, use KIT, and if online, use PhET.